Organizational culture and innovation: the case of the Namibian National Institute for Educational Development - Piepmeyer, Gernot Maximilian (Rhodes University, Faculty of Education, Department of Education, 2009)
The purpose of my research is to diagnose the organizational culture of the National Institute for Educational Development [NIED] , in particular to determine whether it is conducive to innovation, as was envisaged at the time of its inception. The diagnosis of NIED's organizational culture was done by using a hybrid qualitative and quantitative case study. A questionnaire, the Cameron and Quinn's Organizational Culture Assessment Instrument [OCAI], was given to all professional members at NIED, while six members of the NIED organization were interviewed. It emerged from the data, first, that the characteristics of the dominant NIED culture, using Cameron and Quinn's six dimensions of culture that produced an "overall culture profile" of NIED, are not likely to enhance innovativeness. Nevertheless, there is a strong preference towards a culture type favourable to innovation. Second, there are cultural factors antithetical to an innovative organizational culture. These include poor information flow and a lack of communication, negligible crossfunction interaction and freedom, and constraining hierarchical and bureaucratic structures. Third, NIED has, in the form of a "green paper," a set of critical norms, values and assumptions that characterize the culture of innovative organizations. Finally, there is evidence of the presence of cultural characteristics conducive to an innovative organizational culture. These include: learning how to learn; being pro-active in initiating change and innovativeness; and sustaining momentum, consistency and perseverance. The discrepancy between the existing organizational culture and the preferred organizational culture revealed by the overall cultural profile can be explained by the fact that the norms, values and assumptions that characterize the culture of innovative organizations and the cultural characteristics conducive to an innovative organizational culture are not fully infused into the whole organization. There is a tension between NIED's bureaucratic nature and its innovative mission. Organizational culture change, where NIED's structures and processes are aligned with its espoused vision and mission, is needed in order for it to be better placed to achieve its original pioneering mandate.
Keywords: National Institute for Educational Development (Namibia); Corporate culture -- Namibia; Organizational behavior -- Namibia; Technological innovations -- Namibia; Education -- Namibia